2021
DOI: 10.1371/journal.pone.0260447
|View full text |Cite
|
Sign up to set email alerts
|

Persistent eczema leads to both impaired growth and food allergy: JECS birth cohort

Abstract: Skin inflammation leads to altered cytokine/chemokine production and causes systemic inflammation. The systemic mechanism of atopic dermatitis (AD) is recognized to affect systemic metabolism. This study aimed to examine the relationship between early-onset persistent eczema and body weight, height, and body mass index (BMI), in addition to food allergy in a birth cohort among infants. This study design was a nationwide, multicenter, prospective birth cohort study—the Japan Environment and Children’s Study (JE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Below, we review recent epidemiological studies on pediatric allergic diseases in Japan. A nationwide survey of approximately 60,000 people (the Japan Environment and Children’s Study: JECS) reported atopic dermatitis in 18.5% of 1-year-olds and 14.7% of 3-year-olds, and physician-diagnosed food allergies in 6.6% and 6.3% of respondents, respectively [ 37 ]. In an online nationwide survey of 633 children aged 2–6 years, 16.7% of caregivers reported atopic dermatitis by ISAAC, and 16.7% also reported physician-diagnosed food allergy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Below, we review recent epidemiological studies on pediatric allergic diseases in Japan. A nationwide survey of approximately 60,000 people (the Japan Environment and Children’s Study: JECS) reported atopic dermatitis in 18.5% of 1-year-olds and 14.7% of 3-year-olds, and physician-diagnosed food allergies in 6.6% and 6.3% of respondents, respectively [ 37 ]. In an online nationwide survey of 633 children aged 2–6 years, 16.7% of caregivers reported atopic dermatitis by ISAAC, and 16.7% also reported physician-diagnosed food allergy [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the eczema seen at this age may be much more influenced by the season of observation. In Japan, hot and humid conditions in summer are associated with the prevalence of eczema in 1 month olds [ 47 49 ]. In our study, the prevalence was particularly high in 1 month olds (61.0%) compared with older infants, probably because eczema at this age shows a high degree of clinical heterogeneity, similar to other forms of eczema such as seborrheic dermatitis, intertrigo, and diaper dermatitis.…”
Section: Discussionmentioning
confidence: 99%
“…“Anemia” was defined by a positive response to the question “Has your child ever been diagnosed with anemia by a doctor since the age of 2 years?” The variables used in the analysis included dichotomous variables (smoking exposure (yes or no), maternal allergic history (yes or no), parental education levels (low vs. normal or high), family income (<4 or ≥4 million JPY per year), pet keeping (yes or no), birth weight (<2500 or ≥2500 g), sex (boys or girls), premature birth (<37 or ≥37 weeks), breastfeeding (yes or no), sleeping time (<11.5 or ≥11.5 h), kindergarten (yes or no), and parity (nulliparous or multiparous)) and a continuous variable (z score of body mass index (BMI) at 2 years). We calculated z scores for BMI using the LMS method, with age- and sex-specific values of L, M, and S obtained from the Japanese growth curve criteria [ 19 , 20 , 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%